Administration of women prisoners in Orissa: Problems and issues (Note) - Mishra, Sabita; Mohanty, Amarendra (2002)
Conditions of women prisoners in the jails across the country is far from satisfactory. The atmosphere and living conditions there do not seem to fulfill reformative or deterrent purpose behind the detention. This note has focused attention on the situation with special reference to the women inmates lodged in the prisons of Orissa. - Reproduced.
Keywords: Note; Women prisoners - India - Orissa; Women - India - Orissa; Women prisoners